IMPROVING STUDENTS’ SPEAKING ABILITY BY USING WHOLE BRAIN TEACHING (WBT) METHOD AT THE FIRST YEAR STUDENTS’ OF SMP NEGERI 1 BARAKA - St Asmayanti; Rezcy Amalia (Universitas Muhammadiyah Makassar, 2014)
The objectives of the research were to find out the improvement of the students’ speaking accuracy and the improvement of the students’ speaking fluency through the use of Whole Brain Teaching (WBT) Method at the first year students’ of SMP Negeri 1 Baraka. This research used Classroom Action Research that consisted two cycles. The research population was the first year of SMP Negeri 1 Baraka academic year 2012. The sample of this research consisted of 30 students.The researcher obtained the data by using speaking test and observation sheet. The result of this research indicated that the improvement of the students’ speaking accuracy was 6.5 classified as good and the improvement of the students’ speaking fluency was 6.9 classified as good. It could be stated that the students’ speaking ability through the use of Whole Brain Teaching (WBT) Method at the first year students’ of SMP Negeri 1 Baraka improved to a good level after test in the second cycle.